Implementation of Community-Based Total Sanitation Policy in Bengkayang District - Yulius Yohanes; Ida Rochmawati; Rusdiono, Rusdiono (International Journal of Education, Vocational and Social Science, 2024)
Law of the Republic of Indonesia No. 36 of 2009 concerning Health, Article 17 paragraph 1 states that the government is responsible for the availability of access to information, education, and health service facilities to improve and maintain the highest possible degree of health. In addition, Article 168 states that to carry out effective and efficient health efforts, health information is needed, which is carried out through information systems and through cross-sector cooperation, with further provisions even regulated by Government Regulations. Meanwhile, Article 169 states that the government provides convenience to the public to gain access to health information in an effort to improve the degree of public health. Community-Based Total Sanitation (STBM) is an approach to change hygienic and sanitary behavior through community empowerment by triggering. The implementation of STBM aims to realize hygienic and sanitary community behavior independently in order to improve the highest degree of public health (Permenkes RI No. 3 of 2014). In this research method, researchers use a type of descriptive research with qualitative analysis because it is considered more appropriate in describing various phenomena, facts, and existing data in order to be more detailed about the implementation process, implementors / officials involved, target group responses and provide an accurate picture of the various obstacles faced. The results of the study explained that villages that implement STBM, within the scope of villages in Bengkayng District, STBM is still very low, this is due to the lack of frequency of triggering carried out by puskesmas and health offices, limited funds and low community response. The lack of success of the STBM program from the triggering process to post-triggering is because the community is difficult to collect so that the monitoring and monitoring process is hampered. Keywords: Policy, Community-Based Total Sanitation, Puskesmas Bengkayang District.